Analysis of electromagnetic field emitted by power line currents. (2016) - Bendakir, Abelhakim; Bayadi, Abdelhafid; Dib, Djalel; Azar, Ahmad Tahar
Power lines communication (PLC) uses existing power lines and household wiring for communication for several functions, such as computer networking, utility control systems and smart grid. In some areas, PLC is used to provide internet services to households and small businesses. This is often referred to as broadband over power-lines. The general idea of PLC system is to modulate a radio signal with data and transmit it through overhead power lines in a different band of frequencies. The study of electromagnetic compatibility (EMC) aspects of operation at high frequency of the electrical network is about the electromagnetic radiation of power lines communication (PLC) running on unshielded conductors and their possible effects on other devices and on human health. In this paper, we proposed a computation code based on the HF Schelkunoff formalism for calculating the high frequency electromagnetic field of power transmission lines. The computation results are compared to previous results using NEC-4 software and using the formalism of antennas.